LENGUAS DOMINADAS IDEOLOGÍA Y VIOLENCIA LINGÜÍSTICA EN EL MAPUDUNGUN - Alvarez Vandeputte, Javier (2020)
This article proposes elements for the development of a sociology of minority languages. It raises the need for a dialogue between the social sciences and linguistics for the characterization and the situation of linguistic dominance. For this, he proposes the complementarity between the perspectives of ideologies and linguistic violence. In methodological terms, the article systematizes the literature on linguistic ideologies developed by Krotskity and Silverstein and the works of Pierre Bourdieu on violence and linguistic habitus. Both conceptualizations are reviewed in the light of primary and secondary evidence on the situation of the Mapuche language, Mapudungun, in Chile. The article concludes with a discussion on the sociological possibilities of a linguistic liberation of the indigenous and Mapuche peoples.